Lost and Found in Translation: Readers as Translators - Memon, Nayab Asif; Shah, Sabreena; Raheem, Amna Faisal (Technium Social Sciences Journal, 2022)
In this cosmopolitan era where the distance between different ethnicities and races has collapsed, we find a new form of literature which employs code-switching, examples being diaspora literature. An important notion to consider with regards to bilingual literature is to see what effect it has on the readers because, in this context, the readers become the translators. By leaning on linguistic and sociolinguistic theories about codeswitching as well new findings in translation studies, this study intends to investigate what is lost and found during reading texts like Meatless Days by Sara Suleri and Midnight’s Children by Salman Rushdie when the readers become the translators. Semi-structured interviews were conducted and a thematic analysis was carried out on the qualitative data which found that readers translated code-switching along themes of legitimacy, identity and resistance to western knowledge. It was determined that when readers become translators, they have an unprecedented amount of power to interpret texts.